Design and simulation of robot hand for writing and correction assistant applications. Issue 1 (31st May 2021) - Sri Naga Venkat, Parvatini; Srinath, A.; Santosh Kumar, Gurram Narendra; Vijay, P.; Venkatesh, Rentala
Abstract : Purpose: The design of robot hand for writing and correction assistant applications work will be partially replaced as to develop the remote-assisted robot hand control needed to manipulate all this kind of work. As it is stress and strain full job for all teachers, which needs to bring a sustainable solution, hence robot hand which resembles the human hand which is teleoperated with the remote control is designed. Design/methodology/approach: This work presents the design and simulation of a robot hand for correction assistant applications. To replace the work partially especially for the teachers who are undergoing the paper correction work like putting tick mark, cross mark, allocation of marks, etc. Findings: In this paper the design of the same and its simulation of writing the horizontal line, vertical line and writing number two is presented, in further research, a prototype model and its analysis will be done. Originality/value: The design is been done using the modelling software Creo 5.4 where the design will be used to print the prototype model which is physical using 3D printing technology and controlling and testing will be done on the same prototype model using simple Arduino.